Two new coastal species of Elaphropeza Macquart (Diptera: Hybotidae) from Bali, Indonesia - Grootaert, Patrick; Van De Velde, Isabella; Shamshev, Igor V. (European Journal of Taxonomy, 2015)
Two new species of Elaphropeza Macquart, 1827 are described from the northeast coast of Bali (Indonesia): Elaphropeza triseta sp. nov. belonging to the ephippiata-group and E. balinensis sp. nov. belonging to the biuncinata-group. A COI Neighbour-Joining tree is given for the Southeast Asian Elaphropeza species showing large genetic distances between the species. The morphological characterisation of the ephippiata-group and the biuncinata-group sensu Shamshev & Grootaert 2007 is confirmed.